HPC-ABDS High Performance Computing Enhanced Apache Big Data Stack - Fox, Geoffrey C.; Qiu, Judy; Kamburugamuve, Supun; Jha, Shantenu; Luckow, Andre (2015 15th IEEE/ACM International Symposium on Cluster, Cloud and Grid Computing, 2015)
We review the High Performance Computing Enhanced Apache Big Data Stack HPC-ABDS and summarize the capabilities in 21 identified architecture layers. These cover Message and Data Protocols, Distributed Coordination, Security & Privacy, Monitoring, Infrastructure Management, DevOps, Interoperability, File Systems, Cluster & Resource management, Data Transport, File management, NoSQL, SQL (NewSQL), Extraction Tools, Object-relational mapping, In-memory caching and databases, Inter-process Communication, Batch Programming model and Runtime, Stream Processing, High-level Programming, Application Hosting and PaaS, Libraries and Applications, Workflow and Orchestration. We summarize status of these layers focusing on issues of importance for data analytics. We highlight areas where HPC and ABDS have good opportunities for integration.